PENINGKATAN KUALITAS MINYAK JELANTA MENGGUNAKAN KARBON AKTIF DAN EKSTRAK PUCUK IDAT (Cratoxylum glaucum) - Robby Gus Mahardika; Sito Enggiwanto; Ary Samsiar (Tanjungpura University, 2018)
Silica Waste cooking oil can be used as a soap or biodiesel. Good soaps or biodiesel should be from oils that have low levels of fatty acids and free radicals. However, waste cooking oil has high free fatty acid and free radical, it is necessary to increase the quality of waste cooking oil. One effort to improve the quality of waste cooking oil can use activated carbon as an adsorbent. Decrease in free radicals in cooking oil can use antioxidants from extract pucuk idat (Cratoxylum glaucum). This study aims to see the effect of extract pucuk idat on the process of improving the quality of waste cooking oil. The process of improvement by adding activated carbon and varying the concentration of ethanol extract pucuk idat. Activated carbon used 10% with variation of extract 0,25%; 0,5% and 0,75%. This process followed by stirring for 15 minutes at 80°C, then soaked for 3 days. Oil quality are identified by the method of determining the levels of free fatty acids and acid numbers. The results of this study indicate that extract pucuk idat in ethanol with 0,75% concentration has the lowest free fatty acid and acid number. Extract pucuk idat can improve the quality of waste cooking oil.